Edukasi Pencegahan dan Penanganan Kekerasan Berbasis Gender Online - Eka Nizmi, Yusnarida; Olivia, Yessi; Jamaan, Ahmad; Oktyari Retnaningsih, Umi (Indonesian Journal for Social Responsibility, 2024)
Gender-Based Violence (GBV) and Online Gender-Based Violence (OGBV) behavior are issues that should not be allowed to occur in the educational environment, which should uphold ethical values concerning integrity, accountability, and respect for fellow human beings. Unfortunately, sexual violence continues to occur in various countries, including Indonesia. The purpose of this community service project is to provide Prevention and Management Education on OGBV so that students and educators can understand and identify GBV, especially OGBV. The community service activities were conducted at SMA Negeri 1 Bantan, Bengkalis Regency, by providing basic knowledge about gender and gender inequality that can lead to the emergence of OGBV. The method used in these activities was a workshop that required active participation from male and female students to discuss and provide examples of proactive steps to prevent OGBV. The results of this community service project indicate a 34.81% increase in students' understanding of OGBV. This increase was obtained from the pre-test and post-test results conducted by students after participating in the OGBV education activities. The enhanced understanding of OGBV by students following this community service project highlights the importance of education and awareness regarding OGBV. Consequently, it is hoped that this will contribute to efforts to break the chain of gender-based violence in general.